Corruption in Turbulent Times: a Response to Shocks? - Joël Cariolle (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
Economic instability may trigger ex ante and ex post corruption strategies, respectively resulting from the perception and experience of economic fluctuations. Using measures of export instability reflecting its ex ante and ex post effects, dynamic panel estimations are conducted with corruption perception data covering 62 developed and developing countries over 1985-2005; and cross-section estimations with aggregated data on 22,062 firms' bribe reports in 38 developing countries. Estimations support a positive ex post effect of both positive and adverse sharp export fluctuations on corruption, channeled by restricted credit access and weak democratic institutions. By contrast, a deterrent ex post effect of both positive and negative normal export fluctuations is found, channeled by facilitated credit access and effective democratic institutions. Estimations also support a positive ex ante effect of instability on corruption, especially when access to financial markets is restricted. Therefore, when institutions are dysfunctional, both favorable and adverse shocks may increase corruption prevalence.
Keywords: D10; O11; O12; O17; 330